Designing a Pharmacist Opioid Safety and Intervention Tool - Woods, Brendan (Can J Hosp Pharm, 2020)
BACKGROUND: Despite the recent increase in opioid overdoses across Canada, few pharmacy-led initiatives have been implemented to address issues related to opioid prescribing in the hospital setting. OBJECTIVES: The primary objective of this study was to develop a clinical tool, intended for use by hospital pharmacists and informed by best practices from the literature, that would provide a structured approach to enhancing the safety of opioid prescribing. The secondary objective was to collect pharmacists’ opinions about the feasibility and utility of this tool. METHODS: A comprehensive literature search and pharmacist focus group analysis provided content for development of a candidate clinical tool. This tool was then piloted by clinical pharmacists working on general medical and surgical units in a single hospital. Pharmacists participating in the pilot were invited to complete an online survey concerning their perceptions of the tool. Descriptive statistics were used to analyze the survey results. RESULTS: The literature search and focus group analysis led to development of a candidate clinical tool that focused on Medication review, Optimization, Reassessment, and Education (MORE). It included key risk factors relating to opioid safety, along with suggested mitigating strategies. The MORE tool was piloted for 3 weeks by 14 clinical pharmacists, 9 of whom responded to the subsequent survey. Five respondents indicated that the clinical tool increased their ability to identify risk factors. Five respondents also noted an increase in their ability to identify possible interventions. Most respondents felt that the tool was useful and that it would be feasible to integrate it into their practice; however, they noted that a more streamlined version could improve ease of use. CONCLUSIONS: The MORE tool was well received by clinical pharmacists. Implementation of the tool into routine practice requires additional changes to improve ease of use. Suggestions for modifying and streamlining the tool will be incorporated into future versions.